Epidemiology of sepsis in cancer patients in Victoria, Australia: a population‐based study using linked data - Luc te Marvelde; Ann Whitfield; Jennie Shepheard; Carla Read; Roger L. Milne; Kathryn Whitfield (Elsevier, 2020)
Abstract Objective: To determine the clinical characteristics, outcomes and longitudinal trends of sepsis occurring in cancer patients. Method: Retrospective study using statewide Victorian Cancer Registry data linked to various administrative datasets. Results: Among 215,763 incident cancer patients, incidence of sepsis within one year of cancer diagnosis was estimated at 6.4%. The incidence of sepsis was higher in men, younger patients, patients diagnosed with haematological malignancies and those with de novo metastatic disease. Of the 13,316 patients with a first admission with sepsis, 55% had one or more organ failures, 29% required care within an intensive care unit and 13% required mechanical ventilation. Treatments associated with the highest sepsis incidence were stem cell/bone marrow transplant (33%), major surgery (4.4%), chemotherapy (1.1%) and radical radiotherapy (0.6%). The incidence of sepsis with organ failure increased between 2008 and 2015, while 90‐day mortality decreased. Conclusions: Sepsis in patients with cancer has high mortality and occurs most frequently in the first year after cancer diagnosis. Implications for public health: The number of cancer patients diagnosed with sepsis is expected to increase, causing a substantial burden on patients and the healthcare system.